Upaya Notaris Dalam Menggali Kebenaran Materiil Di Setiap Pembuatan Akta - Siti Khanifah Asfiati (Faculty of Law Universitas Islam Indonesia, 2022)
The problem presented in this writing is the obligation of the notary to dig up the material truth in each deed and in case of the notary is asked for information before the court in regards to the said material truth. This method employed in this research is normative or doctrinal in which the object is statutory regulations with a case and doctrine approach, then the primary legal materials are statutory regulations and secondary legal materials are books and journals. The results of this study conclude first, applying the provisions of the Notary Position Law (Undang-Undang Jabatan Notaris, UUJN) and its amendment, the principle of prudentiality in the oath and obligations of a notary, the principle of good governance and the principle of implementing the duties of a notary, providing legal counseling, examining all files carefully and rightfully against the requirements for making a deed even going into the field, the deed must be complete, clear, valid and correct, make good use of technological advances, as well as witnesses from the applicants. Second, the role of the notary in court in relation to material truth, that is, the notary as a witness in court proceedings in connection with the deed he made provides information regarding the procedure for drawing up the deed, the relationship between the applicant and the notary and the position of the notary's office or regime. The author suggests that the present problem in order to dig up the material truth by a notary, government support is needed regarding further regulation in order to realize legal certainty and educate the public that a notary is a law enforcement officer, especially civil law.Key Word: Notary, Material Truth, Authentic Deed AbstrakPermasalahan dalam penulisan ini adalah kewajiban notaris dalam menggali kebenaran materiil di setiap pembuatan akta dan bagaimana jika notaris diminta keterangan dalam pengadilan mengenai kebenaran materiil tersebut. Metode penelitian ini adalah normatif atau doktrinal yang objeknya adalah peraturan perundang-undangan dengan pendekatan kasus dan doktrin. Bahan hukum primer adalah peraturan perundang-undangan dan bahan hukum sekunder ialah buku serta jurnal. Hasil penelitian ini menyimpulkan pertama, menerabkan ketentuan UUJN maupun UUJNP, asas saksama atau kehati-hatian dalam sumpah dan kewajiban notaris, asas pemerintahan yang baik maupun asas pelaksanaan tugas jabatan notaris, memberikan penyuluhan hukum, memeriksa segala berkas dengan teliti dan benar terhadap syarat pembuatan akta bahkan sampai terjun ke lapangan, akta harus lengkap, jelas, absah dan benar, memanfaatkan kemajuan teknologi dengan baik, serta saksi dari penghadap. Kedua, peran notaris dalam persidangan sehubungan dengan kebenaran materiil yaitu notaris sebagai saksi dalam persidangan peradilan sehubungan dengan akta yang dibuatnya memberikan keterangan mengenai prosedur pembuatan akta, hubungan antara penghadap dan notaris dan kedudukan kantor atau wilayah jabatan notaris. Saran penulis dari permasalahan tersebut adalah bahwa demi menggali kebenaran materiil oleh notaris dibutuhkan dukungan pemerintah tentang pengaturannya lebih lanjut demi terwujudnya kepastian hukum dan mengedukasi masyarakat bahwa notaris adalah aparat penegak hukum khususnya hukum perdata.Kata-kata Kunci: Notaris, Kebenaran Materiil, Akta Autentik